Health literacy as a key for effective preventive medicine - Santos, Paulo (Cogent social sciences, 2017)
Background: A preventive approach in health care aims to anticipate the natural history of the diseases and to define break points where the procedures may act to change future events, on the limit of the patient’s free will. Patient is an active agent and the main responsible for his/her own health status. The way to achieve the best integration of the providers’ prescriptions and the patients’ decisions is through education, aiming to increase the literacy status. Body of abstract: Higher levels of literacy for health allow better health decisions, stronger commitment with them and superior levels of efficiency. Patients have to possess enough information enabling its incorporation in free and clear decision-making. In preventive approach, literacy contributes to maximize the profit of health investment and to rationalize the available resources by ceasing some old-fashioned and inadequate technologies, thus contributing to sustainability of health systems. Conclusion: The improvement of patients’ health literacy is crucial. Higher literacy means better health outcomes, both in an individual point of view as for general population, in every levels of preventive approach. Thus, literacy is a relevant determinant of individual health and a public health priority.